PENGEMBANGAN PERANGKAT PEMBELAJARAN BLENDED LEARNING MATERI ARITMATIKA SOSIAL BERBASIS GEOGEBRA CLASSROOM - Ni Komang Swandari; Victor R. Sulangi; Ontang Manurung (ADIBA : JOURNAL OF EDUCATION, 2022)
This study aims was to develop blended learning tools for social aritmetic using the Geogebra Classroom and to determine the quality of the developed learning tools in term ofvalidity, practicality and effectiveness. This research model which consists of Analysis, Design, Development, Implementation, and Evaluation. The percentage of validity of the results of the assessment of the threee xperts respectively for RPP 84,28%, 80% and 91,428% and for LKPD 84,70%, 83,53% and 91,76% where the results of the first and second expert assessment are in the valid criteria while the results of the third expert’s assessment are in very valid criteria. The practicality of learning tools based on the average student response results was 87% with very practical criteria, while the teacher response results for lesson plans was 88,57% and for LKPD was 90,59% with very practical criteria. The effectiveness of learning devices based on student criteria. In conclusion, the learning tools develoved was valid, practical, and effective foruse in the learning process.